Constituent Postponement in Biblical Hebrew Verse - Redd, John Scott (Abhandlungen für die Kunde des Morgenlandes, 2014)
What are the elements of Biblical Hebrew (BH) verse? Much headway has been made in terms of describing the features and devices that find expression in BH verse, but there is more to be said particularly about the distinction between verse and prose. Though BH verse is governed by a terse poetic line, it also exhibits "relaxed" syntactic structure, wherein certain syntactic constructions that would be unviable in prose are acceptable. One such construction is the occurrence of constituent postponement in the verbal clause, such as postverbal subject- and object-postponement as well as verb-pos